THE ROLE OF ETHICAL AND LEADERSHIP ON EMPLOYEES PERFORMANCE TOWARD ORGANISATION COMMITMENT - Tika Dwi Fatmawati; Junaidi; M. Yusuf Q.; Andi Nadhirah (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Organizations, including the government sector, have faced ethical issues and the challenge of providing the best service to society. Government stakeholders need to be concerned about performance and ensure that excellent corporate governance (GCG) aligns with the central government vision. The research stemmed from the identification of a problem where the disciplinary spirit of the ASN was not adequately supported by a strong leadership style and motivation, resulting in government employees (ASN) still not fully understanding the concept of the CGG. The objectives of the study are to identify the impact of leadership styles, work discipline, and work motivation on ASN performance. This study invited 115 participants and used structural equation modelling (SEM) to examine research hypotheses. The Hayes bootstrapping approach was used to examine employee commitment as a mediator variable. The empirical findings demonstrate that ethics and trust have a positive and significant impact on employee job satisfaction, both directly and indirectly, leading to increThe government should establish clear rules and laws to uphold the ethical standards of employees’ work, thereby enhancing public trust and enhancing government credibility. ent credibility. This study validates the work of government employees (ASN) in a specific region of Indonesia; therefore, additional research is necessary to expand the study’s scope and achieve a comprehensive outcome.